Low-density lipoprotein specifically binds glycoprotein IIb/IIIa: A flow cytometric method for ligand-receptor interaction - TETİK, ŞERMİN (SAGE PUBLICATIONS INC, 2008)
Primary platelet aggregation requires agonist-mediated activation of membrane receptor glycoprotein (GP) IIb/IIIa, binding of fibrinogen to GpIIb/IIIa, and cellular events after fibrinogen binding. This study investigated whether fibrinogen receptor GpIIb/IIIa is also the binding site for low-density lipoprotein (LDL) in platelets by using GpIIb/IIIa-coated polystyrene microbeads incubated with various concentrations of fluorescein isothiocyanate (FITC)-labeled ligands. Binding was assayed by flow cytometry. Binding of fibrinogen (Fg)-FITC and LDL-FITC to GpIIb/IIIa coated microbeads was concentration dependent, reaching saturation. Binding of LDL-FITC to GpIIb/IIIa coated microbeads was inhibited by fibrinogen. Binding of LDL-FITC or Fg-FITC to freshly isolated platelets gave similar results as those of GpIIb/IIIa coated microbeads. Glycoprotein IIb/IIIa, the fibrinogen receptor on platelets is also one of the binding sites of LDL on platelets. This rapid and reliable flow cytometric technique using coated microbeads may be used as a first step for the study of all ligand receptor interactions.
Keywords: low-density lipoprotein; glycoprotein IIb/IIIa; platelets; flow cytometry; microbeads; PLATELET INTERACTION; ACTIVATED PLATELETS; GPIIB-IIIA; IIB-IIIA; LDL; PURIFICATION; AGGREGATION; FIBRINOGEN; THROMBOSIS; SITES